2016
DOI: 10.2174/1874070701610010198
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Thermostable Cellulase from Bacillus licheniformis Strain Vic Isolated from Geothermal Wells in the Kenyan Rift Valley

Abstract: Cellulolytic microorganisms such as fungi and bacteria are responsible for much of the cellulose degradation in soils. Despite the vast number of cellulase producers, there is a deficiency of microorganisms that can produce significant amount of the three components of a cellulase system. i.e. CMCases, exoglucanases and β-glucosidases to efficiently degrade cellulose to fermentable products.Soil samples were collected from two sites of the Kenyan Rift valley; Hell's gate National Park and a geothermal well in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The pH is a factor that has a significant effect on the stability of enzymatic reaction [28]. The enzymes that are produced from different bacteria allow them to have different optimum pH for their activity.…”
Section: Issn 2087-2852 E-issn 2338-1655mentioning
confidence: 99%
“…The pH is a factor that has a significant effect on the stability of enzymatic reaction [28]. The enzymes that are produced from different bacteria allow them to have different optimum pH for their activity.…”
Section: Issn 2087-2852 E-issn 2338-1655mentioning
confidence: 99%
“…Cellulose is the most abundant biopolymer in nature and forms the major component of plant biomass (Yin et al, 2010;Sadhu et al, 2013;Kilo et al, 2016). It is a linear polysaccharide polymer of β-1,4-glycosidic bonds and its crystalline structure is stabilized by intramolecular and intermolecular hydrogen bonds (Hikaru et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, cellulose is the main component of the cell wall of most land plants, where it is found as microfibrils, forming a structurally strong framework in cell walls [45]. Our results demonstrated that cellulase enzymes are inducible in both strains.…”
Section: Discussionmentioning
confidence: 57%